Recurrence stroke of ischemic stroke patients in Thailand: a nationwide study - Krissana Aunthakot; Wongsa Loahasiriwong; Somsak Tiamkao (Intelektual Pustaka Media Utama, 2023)
Stroke is a global health problem and a leading cause of mortality and disability. Patients who survived an initial stroke are at risk for a recurrence stroke of the same type or another. However, few studies have documented at a national level. This research aimed to investigate the magnitude of recurrence stroke among ischemic stroke patients. This descriptive study used the data from neurology database collected between 2006 to 2020 in hospitals under the National Health Security System (NHSO) of Thailand. Among 511,322 ischemic stroke patients, recurrence of all types of strokes occurred in 85,968 patients or 16.81% (95% CI: 16.71-16.92). The prevalence was highest among patients with hypertension and diabetes mellitus at 18.89% (95% CI: 18.54-19.26), atrial fibrillation at 18.79% (95% CI: 18.42-19.15), and ischemic heart disease at 18.59% (95% CI: 18.05- 19.15). Furthermore, patients who received recombinant tissue plasminogen activator (rt-PA) treatment (12.15% %, 95%CI: 11.75-12.55) and rehabilitation (14.39%, 95% CI: 14.25-14.54) had a lower prevalence. Co- morbidities were an important factor had a high recurrence and treatment factors that patients receive had a low recurrence. Therefore, policymakers and health institutions could use these findings to implement treatment and monitoring policies for recurrence stroke.